Radiation Response of Murine Embryonic Stem Cells - Hellweg, Christine E. (Cells, 2020)
To understand the mechanisms of disturbed differentiation and development by radiation, murine CGR8 embryonic stem cells (mESCs) were exposed to ionizing radiation and differentiated by forming embryoid bodies (EBs). The colony forming ability test was applied for survival and the MTT test for viability determination after X-irradiation. Cell cycle progression was determined by flow cytometry of propidium iodide-stained cells, and DNA double strand break (DSB) induction and repair by γH2AX immunofluorescence. The radiosensitivity of mESCs was slightly higher compared to the murine osteoblast cell line OCT-1. The viability 72 h after X-irradiation decreased dose-dependently and was higher in the presence of leukemia inhibitory factor (LIF). Cells exposed to 2 or 7 Gy underwent a transient G2 arrest. X-irradiation induced γH2AX foci and they disappeared within 72 h. After 72 h of X-ray exposure, RNA was isolated and analyzed using genome-wide microarrays. The gene expression analysis revealed amongst others a regulation of developmental genes (Ada, Baz1a, Calcoco2, Htra1, Nefh, S100a6 and Rassf6), downregulation of genes involved in glycolysis and pyruvate metabolism whereas upregulation of genes related to the p53 signaling pathway. X-irradiated mESCs formed EBs and differentiated toward cardiomyocytes but their beating frequencies were lower compared to EBs from unirradiated cells. These results suggest that X-irradiation of mESCs deregulate genes related to the developmental process. The most significant biological processes found to be altered by X-irradiation in mESCs were the development of cardiovascular, nervous, circulatory and renal system. These results may explain the X-irradiation induced-embryonic lethality and malformations observed in animal studies.